Age, growth and per-recruit stock assessment of southern mullet Chelon richardsonii in Saldanha Bay and Langebaan Lagoon, South Africa - Horton, M; Parker, D; Winker, H; Lamberth, SJ; Hutchings, K; Kerwath, SE (African journal of marine science, 2019)
The southern mullet Chelon richardsonii (Mugilidae) is the main target species of the inshore net fishery (gillnet and beach-seine) on the west coast of South Africa. The stock has displayed symptoms of overfishing, with a 28% reduction in the standardised catch per unit effort (CPUE) between 2008 and 2016, and a 36.5-mm reduction in mean total length (TL) of fish in the commercial catch between 1998 and 2017. The socioeconomic importance of the inshore net fishery and concern regarding stock status necessitated an assessment of the C. richardsonii stock. This work presents an update of the life-history parameters and the first stock assessment of C. richardsonii at the centre of its distribution-Saldanha Bay and Langebaan Lagoon-using CPUE standardisation and per-recruit analysis. The sexes exhibited distinctive growth, with females growing larger, and their length-at-first-maturity was estimated at 205 mm TL, corresponding to age 2 years. Estimated natural mortality was 0.718 y -1 , total mortality was 1.599 y -1 , and fishing mortality was 0.881 y -1 . Current spawner- biomass-per-recruit was estimated at 24.5% of the pristine (unfished) levels, indicating a stock at risk of recruitment failure. An increase in the minimum stretched mesh size of the gillnets to 51 mm and a reduction in fishing mortality to 0.60 y -1 (approximately 30%) would facilitate the recovery of the spawner biomass to the target of 40% of pristine (SB 40 ).